Aqueous extract of Sargentodoxa cuneata alleviates ulcerative colitis and its associated liver injuries in mice through the modulation of intestinal flora and related metabolites - Xu, Feng; Yu, Piao; Wu, Hongmei; Liu, Mei; Liu, Hongyun; Zeng, Qian; Wu, Dengli; Wang, Xiangpei (Frontiers in Microbiology, 2024)
Background: Ulcerative colitis (UC) is a refractory disease in the world. Liver injury can be found clinically with UC, now it is found that the gut dysbiosis is an important mechanism in the pathogenesis of UC. Sargentodoxa cuneata has been used as a traditional Chinese medicine and is commonly used clinically for the treatment of UC. The main objective of this study was to investigate the intrinsic mechanisms of Sargentodoxa cuneata in the treatment of UC and its associated liver injuries from the perspective of intestinal flora and related metabolites. Methods: A ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) was used to identify the components in aqueous extract of Sargentodoxa cuneata (AESc). Mice with UC induced by dextran sulfate sodium (DSS) were used to study the effects of AESc on UC and its associated liver injuries. Further, 16S rRNA sequencing and quantitative analysis were performed on intestinal contents, and correlation analysis of intestinal flora with short-chain fatty acids (SCFAs) and organic acids was performed. Results: A total of 114 compounds were identified in AESc. AESc improved disease activity index scores, liver index, and colon length in mice with UC, and had a good protective effect on intestine and liver injuries. Moreover, the administration of AESc regulated gut microbiota dysbiosis and the levels of few SCFAs and organic acids in mice with UC. In addition, the correlation analysis results showed that the Megamonas and Bifidobacterium were the key intestinal flora related to levels of differential SCFAs and organic acids in the mice with UC after AESc intervention. Conclusion: AESc has a good protective effect on UC and it related liver injuries. Modulation of the intestinal flora and its metabolites (SCFAs and few organic acids) is an important pathway for AESc in the treatment of UC, and also provide a rationale for the clinical use of Sargentodoxa cuneata in the treatment of UC.